Formulation of multicomponent inclusion complex of cyclodextrin-amino acid with Chrysin: Physicochemical characterization, cell viability and apoptosis assessment in human primary glioblastoma cell line - Wael A. Mahdi; Mohammed Mufadhe Alanazi; Syed Sarim Imam; Sultan Alshehri; Afzal Hussain; Mohammad A. Altamimi; Sulaiman S. Alhudaithi (Elsevier, 2023)
Chrysin (CR) is a water-insoluble drug reported for different therapeutic effects. The microwave irradiation method was used in this study to create a multicomponent inclusion complex (CR-MC) containing CR (drug) and carrier hydroxyl propyl beta cyclodextrin (HP β CD) and L-arginine (LA). The prepared inclusion complex (CR-MC) was evaluated for dissolution study and results were compared with chrysin physical mixture (CR-PM). Further, the samples were assessed for infra-red (IR), nuclear magnetic resonance (NMR), differential scanning calorimeter (DSC), scanning electron microscope (SEM) and molecular docking. Finally, the cell viability, reactive oxygen species and flow cytometer studies were also assessed to check the potential of the prepared inclusion complex on the human primary glioblastoma cell line (U87-MG cell). The phase solubility findings revealed a stability constant (773 mol L−1) as well as a complexation efficiency of 0.027. The dissolution study displayed a significant increase in CR release from CR-MC (99.03 ± 0.39%) > CR-PM (70.58 ± 1.16%) > pure CR (35.29 ± 1.55%). NMR and IR spectral data revealed no interaction between CR and carriers. SEM and DSC study results revealed the conversion into amorphous form. The molecular docking results illustrated a high docking score, which supports the findings of complex formation. The cell viability, reactive oxygen species, and flow cytometry studies results showed enhanced activity from CR-MC against the tested human primary glioblastoma cell line. From the results it has been observed that chrysin solubility significantly increased after complexation and there in vitro activity also enhanced against cancer cell line.